Desarthrodesis of ankle and subtalar stabilization with a flexible system: a functional surgical proposal - Guerrero-Forero, Alvaro Santiago; de la Torre, Otilia Gallegos; Gómez-Carlín, Luis A. (Journal of the Foot & Ankle, 2020)
Patients who have undergone ankle arthrodesis frequently suffer from alterations in the adjacent joints and functional limitations. A 56-year-old female with a 22-year history of ankle arthrodesis underwent a conversion of ankle arthrodesis to total ankle replacement, followed by stabilization of the subtalar joint with a flexible system. The FAAM scale preoperative and eight-week postoperative scores were 39/100 and 88/100, respectively, and the SF-36 scale preoperative and eight-week postoperative scores were 37.52 and 73.61, respectively. In this case, ankle function was recovered after the conversion of ankle arthrodesis to total ankle replacement. With this technique, we obtained satisfactory functional results. Level of Evidence V; Therapeutic Study, Expert Opinion.